2008
DOI: 10.1007/bf03246110
|View full text |Cite
|
Sign up to set email alerts
|

Some applications of zirconium(IV) tetrachloride (ZrCl4) and zirconium(IV) oxydichloride octahydrate (ZrOCl2.8H2O) as catalysts or reagents in organic synthesis

Abstract: Both ZrCl 4 and ZrOCl 2 .8H 2 O are commercially available solid chemicals. Due to their low toxicities (LD 50 [ZrCl 4 oral rate] = 1688 mg/kg), (LD 50 [ZrOCl 2 .8H 2 O oral rate] = 2950 mg/kg), low costs, ease of handling, high activity, the zirconium(IV) compounds are potential green catalysts or reagents which are of importance from different views. In this review we have paid attention to the applications of these compounds as reagents or catalysts in Friedel-Crafts reactions, Fries rearrangements, reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 131 publications
(96 reference statements)
0
11
0
Order By: Relevance
“…They are known to catalyze different organic reactions, such as Ferrier rearrangement (Swamy et al, 2004;Smitha and Sanjeeva Reddy, 2004), Fries rearrangement (Harrowven and Dainty, 1996), Friedel-Crafts acylation (Heine et al, 1946), sodium borohydride reduction (Itsuno et al, 1988(Itsuno et al, , 1990Purushothama Chary et al 1999, 2000, multicomponent condensations affording dihydropyrimidinones (Venkateshwar Reddy et al, 2002) and -aryl--mercaptoketones (Kumar and Akanksha, 2007), Pechmann reactions (Karami and Kiani, 2011) etc. (Curini et al, 2004;Firouzabadi and Jafarpour, 2008;Zhang and Li, 2009). Catalytic activity of different zirconium compounds in Michael conjugate addition of nucleophiles to α,βunsaturated carbonyls has also been recognized by organic chemists and used in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are known to catalyze different organic reactions, such as Ferrier rearrangement (Swamy et al, 2004;Smitha and Sanjeeva Reddy, 2004), Fries rearrangement (Harrowven and Dainty, 1996), Friedel-Crafts acylation (Heine et al, 1946), sodium borohydride reduction (Itsuno et al, 1988(Itsuno et al, , 1990Purushothama Chary et al 1999, 2000, multicomponent condensations affording dihydropyrimidinones (Venkateshwar Reddy et al, 2002) and -aryl--mercaptoketones (Kumar and Akanksha, 2007), Pechmann reactions (Karami and Kiani, 2011) etc. (Curini et al, 2004;Firouzabadi and Jafarpour, 2008;Zhang and Li, 2009). Catalytic activity of different zirconium compounds in Michael conjugate addition of nucleophiles to α,βunsaturated carbonyls has also been recognized by organic chemists and used in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic activity of different zirconium compounds in Michael conjugate addition of nucleophiles to α,βunsaturated carbonyls has also been recognized by organic chemists and used in organic synthesis. In this regard, both types of nucleophiles -those with a heteroatom as the nucleophilicity carrier and C-nucleophiles were successfully used (Curini et al, 2004;Firouzabadi and Jafarpour, 2008;Zhang and Li, 2009). In continuation of our permanent interest in both the electrochemical generation of catalysts (Vukićević et al, 1991(Vukićević et al, , 1998 and ferrocene chemistry (Vukićević et al, 2002;Damljanović et al, 2014), we recently reported on a new and versatile method for the electrochemical generation of a catalyst capable of promoting the Ferrier rearrangement and hetero-Michael conjugate addition of N-and S-nucleophiles to methyl vinyl ketone, using a sacrificial zirconium anode (Stevanović et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, in the present study, we report here the use of zirconyl nitrate as eco-friendly water-soluble Lewis acid catalyst for the synthesis of substituted benzimidazole. In recent years, Zr(IV) compounds have gained special attention as catalysts in organic synthesis, and some of these are stable in aqueous media [29][30][31]. In the continuation of our interest in synthesis of nitrogen-containing heterocyclic compounds [32], herein wefoundedthe application of ZrO(NO 3 ) 2 as a Lewis acid catalyst for the synthesis of substituted benzimidazoles viathe condensation reaction between o-phenylenediamine and aldehyde, carboxylic acid derivatives (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Three-component synthesis starting from aldehydes, amines and diethyl phosphite or triethyl phosphite have been reported by using Lewis and Bronsted acid catalysts such as LiClO4 [ 15 ], InCl 3 [ 16 ], AlCl 3 [ 17 ], lanthanide triflates/magnesium sulfate [ 18 ], SbCl 3 /Al 2 O 3 [ 19 ], TaCl 5 -SiO 2 [ 20 ], CF 3 CO 2 H [ 21 ], scandium (tris-dodecyl sulfate) [ 22 ], BF 3 ·Et 2 O [ 23 ], M(OTf) n [ 24 ], and M(ClO 4 ) n [ 25 ], though, many of these methods suffer from some drawbacks such as long reaction times, low yields of the products, requiring stoichiometric amounts of catalysts, costly and moisture sensitive catalysts, and use of highly toxic or toxic catalysts. More recently, ZrOCl 2 ·8H 2 O [ 26 ] or ZrO(ClO 4 ) 2 ·6H 2 O [ 27 ] and TiO 2 [ 28 ] are reported to be effective catalysts for the formation of α -aminophosphonates using a three- component system composing of aldehydes/ketones, amines, and diethylphosphite under neat conditions. Recently, we have reported one-pot three-component synthesis starting from aldehydes, amines and diethylphosphite using FeCl 3 as a catalyst to formation of α -aminophosphonates [ 29 ].…”
Section: Introductionmentioning
confidence: 99%